2016
DOI: 10.1002/term.2175
|View full text |Cite
|
Sign up to set email alerts
|

Algorithm-driven optimization of cryopreservation protocols for transfusion model cell types including Jurkat cells and mesenchymal stem cells

Abstract: This investigation describes the use of a differential evolution (DE) algorithm to optimize cryopreservation solution compositions and cooling rates for specific cell types. Jurkat cells (a lymphocyte model cell type) and mesenchymal stem cells (MSCs) were combined with non-DMSO solutions at concentrations dictated by a DE algorithm. The cells were then frozen in 96-well plates at DE algorithm-dictated cooling rates in the range 0.5–10°C/min. The DE algorithm was iterated until convergence resulted in identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Multicomponent solutions have also been explored and factorial experiments to identify favorable combinations and freezing protocols have shown increased success. 5,6 Previously published work by this group 7 describes algorithm optimization of multicomponent cryopreservative solutions, including molecules that target different aspects of cell protection during freezing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multicomponent solutions have also been explored and factorial experiments to identify favorable combinations and freezing protocols have shown increased success. 5,6 Previously published work by this group 7 describes algorithm optimization of multicomponent cryopreservative solutions, including molecules that target different aspects of cell protection during freezing.…”
Section: Introductionmentioning
confidence: 99%
“…20 However, the concentrations of these cryoprotectants dictate whether they will be stabilizing or destabilizing 21,22 and concentrations that result in stabilization optimums may differ when cryoprotectants are combined. 23 In a previous study, we established our ability to optimize the composition of a multicomponent osmolyte solution 7 using a computational algorithm. The focus of this investigation involves expanding our understanding of multicomponent osmolyte solutions and their ability to preserve cell viability during freezing.…”
Section: Introductionmentioning
confidence: 99%
“…The group agreed that further discussion on the application of such deep systems analysis for cell preparations for cell therapy could assist in the assessment of preservation methods. Furthermore, in-depth studies of different combinations of different culture media and matrices using highthroughput approaches are likely to identify improved preservation and stability of models systems as had been developed for gametes [12,13] (see Box 2 for Recommendation 2).…”
Section: Session 3: Characterization Of Cellular Preparationsmentioning
confidence: 99%
“…In order to improve cell cryopreservation efficiency, previous studies have mainly focused on the optimization of CPA formulation, CPA introduction, and freezing-thawing protocol suitable for different cell types [10,11]. Pollock et al [12] reported the use of a differential evolution algorithm to optimize cryopreservation protocols for Jurkat cells (300 mmol/L trehalose, 10% glycerol, and 0.01% ectoine at 10 °C/min) and mesenchymal stem cells (300 mmol/L ethylene glycol, 1 mmol/L taurine, and 1% ectoine at 1 °C/min), which resulted in post-thawing cell viabilities of 95% and 96%, respectively. However, the optimization of cryopreservation protocol still suffers from two major challenges: (1) unfavorable post-thaw cell viability or functions and (2) safety concerns induced by CPA toxicity.…”
Section: Introductionmentioning
confidence: 99%